2012
DOI: 10.1371/journal.pone.0044047
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetic Background Impacts Disease Outcome During Intrauterine Infection with Ureaplasma parvum

Abstract: Ureaplasma parvum, an opportunistic pathogen of the human urogenital tract, has been implicated in contributing to chorioamnionitis, fetal morbidity, and fetal mortality. It has been proposed that the host genetic background is a critical factor in adverse pregnancy outcome as sequela to U. parvum intra-amniotic infection. To test this hypothesis we assessed the impact of intrauterine U. parvum infection in the prototypical TH1/M1 C57BL/6 and TH2/M2 BALB/c mouse strain. Sterile medium or U. parvum was inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 72 publications
3
39
3
Order By: Relevance
“…experience adverse pregnancy outcomes while others do not, some researchers have attributed these differences in sequelae to the virulence of the infecting serovar (200), the bacterial load present (201,202), or genetic background/ethnicity (203,204). However, these findings are not always consistent, with a recent study by our group demonstrating no correlation between the numbers of Ureaplasma present within placentae, the species/serovar present, or the ethnicity of women infected with Ureaplasma and the incidence or severity of histological chorioamnionitis (62).…”
Section: Ureaplasma Spp As Etiological Agents Of Chorioamnionitismentioning
confidence: 99%
See 3 more Smart Citations
“…experience adverse pregnancy outcomes while others do not, some researchers have attributed these differences in sequelae to the virulence of the infecting serovar (200), the bacterial load present (201,202), or genetic background/ethnicity (203,204). However, these findings are not always consistent, with a recent study by our group demonstrating no correlation between the numbers of Ureaplasma present within placentae, the species/serovar present, or the ethnicity of women infected with Ureaplasma and the incidence or severity of histological chorioamnionitis (62).…”
Section: Ureaplasma Spp As Etiological Agents Of Chorioamnionitismentioning
confidence: 99%
“…BALB/c mice typically display a Th1/M1-dominant immune profile, whereas the immune profile of C57BL/6 mice is consistent with a Th2/M2 bias (203). These differences have enabled researchers to examine the immunopathogenic role of a skewed Th1/M1 or Th2/M2 response in Ureaplasma chorioamnionitis.…”
Section: The Immune Response To Ureaplasma Chorioamnionitis: Harmful mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the observed leukocytosis is associated with low immunity (Tegtmeier et al 1999, Ohlsson et al 1993, Honma et al 2007). Von Chamier et al (2012) reported that intra-uterine experimental infection in mice with U. parvum was able to induce sepsis with severe fetal infl ammatory response. Thus, the host immune response could be a determinant factor in the severity of disease, since immunosuppressed animals are more likely to develop a systemic response (Famuyide et al 2009, Peng et al 2013.…”
Section: Discussionmentioning
confidence: 99%